Pemanfaatan Terapi Murotal Al-Qur’an Sebagai Terapi Non Farmakologi Terhadap Penurunan Nyeri Pasien Post Operasi : Literatur Review - Fratama, Ferry Fadli; Fauziah, Erna; Hutagaol, Rutmauli (Politeknik Kementerian Kesehatan Banjarmasin, 2024)
Background : Surgery is an invasive treatment procedure that aims to save the patient's life, prevent disability and complications. Objective: The purpose of this article is to find out the benefits of Qur'anic murotal therapy on reducing pain in postoperative patients. Methods: The method used is literature review search carried out through Google scholar, Science direct and PubMed with the article search method using PICOTT. Article searches are limited to full-text articles, national journals and international journals, published in 2019-2023. The search results obtained 627 articles from all databases, 622 Google scholar articles and 5 PubMed articles. Results: The results of this study found 5 articles that fit the inclusion and exclusion criteria. The results of the literature review show the results of each article, namely there is Qur'anic murotal therapy to reduce postoperative patient pain. It is recommended to health workers, especially nurses, to be able to apply Qur'anic murotal therapy as a complementary therapy or non-pharmacological therapy to reduce postoperative patient pain. Keywords: Qur'anic murotal therapy, Pain, Post surgery